[OP.3A.07] DROSPIRENONE WITH ESTRADIOL FOR POSTMENOPAUSAL WOMEN WITH HYPERTENSION: A SYSTEMIC REVIEW AND META-ANALYSIS. (September 2016) - Zhao, X.; Yu, J.
Abstract : Objective: To assess the efficacy and safety of a novel hormone therapy drospirenone combined 17-β-estradiol (DRSP/E2) in postmenopausal hypertensive women. Design and method: We searched the following databases including PubMed, Cochrane Library, EMBASE, Web of Science and added literature by manual retrieval. The randomized controlled trials (RCT) about the drospirenone with 17-β-estradiol for postmenopausal women with hypertension were included. Studies were screened independently by two researches according to the inclusion and exclusion criteria; data were extracted; the methodological quality was evaluated by Cochrane handbook 5.1.0 and meta-analyses were conducted by using RevMan 5.3.0 software. Results: Five studies involving 1263 patients were included. The results of Meta-analysis showed that DRSP/E2 was superior in reducing blood pressure (BP), the clinic BP was reduced significantly compared with the control group (systolic BP, MD = –5.74, 95% CI: −7.67 to −3.82, P < 0.00001; diastolic BP:MD = –5.62, 95% CI: −6.82 to −4.41, P < 0.00001). The change of 24-h mean BP in DRSP/E2 shows a statistically significant difference (24-h systolic BP, MD = –5.77, 95% CI: −7.85 to −3.68, P < 0.00001; 24-h diastolic BP:MD = –3.59, 95% CI: −4.92 to −2.27, P < 0.00001); There were no significant changes from baseline in potassium levels (SD = –0.02, 95% CI: −0.07 to 0.04, P = 0.50) on DRSP/E2 compared with control group. There was no statistical difference in the incidence of adverse events (RR = 0.59, 95% CI: 0.24 to 1.44, P = 0.25) between DRSP/E2 and control group. Conclusions: The current evidences indicate that DRSP/E2 can significantly lower both systolic blood pressure and diastolic blood pressure in postmenopausal women with hypertension. This characteristic may lead to benefit for blood pressure reduction in this population. As the sample of included RCT is not large enough, the follow-up is short, the larger sample randomized, and controlled trials are required to prove further the curative effect and safety of Drospirenone with 17-β-Estradiol for postmenopausal hypertension.